Observational study of the recent efficacy and economy of itraconazole vs. voriconazole in perioperative pulmonary aspergillosis - Chen, Peng; Zhang, Xiao; Zheng, Xinzhe; Tang, Yang; Song, Yongxiang; Xu, Gang; Ke, Xixian; Chen, Cheng (Frontiers in Surgery, 2025)
BackgroundAntifungal therapy is a common treatment option for pulmonary aspergillosis, but its use to prevent recurrence and relieve symptoms in patients with pulmonary aspergillosis remains controversial. This study aimed to explore the short-term efficacy and cost of itraconazole vs. voriconazole in the treatment of pulmonary aspergillosis during the perioperative period.MethodsWe retrospectively collected the clinical data of 55 patients with pulmonary aspergillosis who underwent surgery and received itraconazole or voriconazole as antifungal therapy between January 1, 2016, and October 31, 2022, at the Department of Thoracic Surgery, Affiliated Hospital of Zunyi Medical University. We analyzed the effects of different antifungal therapies on the incidence of adverse events, short-term efficacy, and cost-effectiveness of pulmonary aspergillosis treatment.ResultsExcept for the younger average age of patients in the itraconazole group, there were no significant differences in baseline characteristics such as sex, BMI, underlying lung disease, accompanying symptoms, and lesion location between the voriconazole and itraconazole groups. There was no significant difference in the incidence of adverse events or short-term efficacy, including recovery, symptom improvement, and recurrence rates, during the administration of the antifungal regimens between the two groups. Regarding economic cost efficiency, there was no significant difference in the median hospitalization costs between the two groups. However, despite the longer antifungal treatment duration in the itraconazole group, the cost of itraconazole was significantly lower than that of voriconazole.ConclusionBoth itraconazole and voriconazole effectively prevented the recurrence of pulmonary aspergillosis. They are similar in terms of the incidence of adverse events and short-term efficacy; however, itraconazole is more economical.